Penerapan Metode Runge-Kutta Orde 4 pada Pemodelan Penularan Penyakit Cacar Monyet - Dian Grace Ludji; Febrya Christin Handayani Buan (Saintek Lahan Kering, 2022)
Monkeypox is a zoonotic infectious disease caused by the monkeypox virus which belongs to the Orthopoxvirus group. This virus was originally transmitted from animals who innfected with the monkeypox virus to humans, especially rodents and primates. In addition, it can also be transmitted between humans. To make it easier to describe the process of the spread of monkeypox, a mathematical model was created. The mathematical model was made by taking several assumptions based on the nature of charateristics of monkeypox, especially on the pattern of the spread of monkeypox. Based on the assumptions made, this model has two parts to the population, namely the human population is divided into four subpopulations and the animal population is divided in two subpopulations. The model produces a system of non-linear equations that is solved using the Runge-Kutta method of orde 4. The result obtained in this study is a simulation in graphical form. Two simulations were carried out using different parameter values. The parameter is the rate of human infection from animals. The simulation results show that when the value of the human infection rate from animals is reduced, the disease will disappear within a certain time. So that, one of the factor that can be suppressed so that the spread of monkeypox is controlled is the rate of human infection from animals.